Characterisation of Optimal Responses to Pulse Inputs in the Bergman Minimal Model. Issue 1 (July 2017) - Townsend, Christopher; Seron, Maria M.; Goodwin, Graham C.
Abstract: The Bergman minimal model is a dynamic model of plasma glucose concentration. It has two input variables - insulin delivery and carbohydrate intake. We investigate the behaviour of plasma glucose concentration predicted by the model given carbohydrate (CHO) inputs and commensurate insulin inputs. We observe that to maintain plasma glucose above a specified minimum concentration results in an unavoidable peak in plasma glucose. Additionally, we specify the timing and magnitude of a bolus pulse to minimise this unavoidable peak in plasma glucose concentration whilst attaining but not going below the desired minimum glucose concentration. Finally, we obtain necessary and sufficient conditions for the glucose concentration to be minimised.